2013
DOI: 10.1371/journal.pone.0073501
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Tuberculosis Treatment, Sputum Smear Conversion and Mortality: A Retrospective Cohort Study in 48 Rwandan Clinics

Abstract: BackgroundAdherence to treatment and sputum smear conversion after 2 months of treatment are thought to be important for successful outcome of tuberculosis (TB) treatment.MethodsRetrospective cohort study of new adult TB patients diagnosed in the first quarter of 2007 at 48 clinics in Rwanda. Data were abstracted from TB registers and individual treatment charts. Logistic regression analysis was done to examine associations between baseline demographic and clinical factors and three outcomes adherence, sputum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
1
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 17 publications
2
55
1
7
Order By: Relevance
“…The findings contrast with those from recent studies in Rwanda that found a lower smear completion rate and poor patient adherence as an independent determinant of mortality. 11,12 Overall treatment outcomes for all new TB cases were similar between the treatment groups and were satisfactory, with cure or treatment completed in 81% of all cases with a known outcome. However, some discrepancies were noted with the data.…”
Section: Public Health Action Fdcs Vs Single-drug Preparations For Tmentioning
confidence: 84%
“…The findings contrast with those from recent studies in Rwanda that found a lower smear completion rate and poor patient adherence as an independent determinant of mortality. 11,12 Overall treatment outcomes for all new TB cases were similar between the treatment groups and were satisfactory, with cure or treatment completed in 81% of all cases with a known outcome. However, some discrepancies were noted with the data.…”
Section: Public Health Action Fdcs Vs Single-drug Preparations For Tmentioning
confidence: 84%
“…Another factor that helps to explain this result is treatment abandonment, which predicts the development of multiple drug resistance (MDR) and, thus, hospitalizations [35].…”
Section: Discussionmentioning
confidence: 99%
“…Beberapa studi melaporkan bahwa kehilangan berat badan setelah akhir bulan pertama terapi, dan tes BTA positif pada akhir bulan kedua terkait dengan kegagalan terapi. 13,14 Pada penelitian ditemukan sebagian besar pasien memiliki keluhan yang kemungkinan terkait dengan ADR dengan gejala yang paling umum adalah mual, muntah dan anoreksia. Hasil ini sejalan dengan beberapa studi yang menyatakan bahwa kejadian ESO/ADR pada pasien TB cukup banyak berkisar antara 4,4-30 % dan bentuknya sangat beragam seperti gangguan gastrointestinal, hepatotoksik, ruam kulit.…”
Section: Pembahasanunclassified
“…Beberapa intervensi yang dapat dilakukan apoteker untuk meningkatkan outcome pasien TB antara lain dengan melalui konseling untuk berhenti merokok, 9,10 pemberian edukasi dan konseling akan meningkatkan pengetahuan dan kepatuhan pasien, 11,12 identifikasi faktor risiko, pengenalan awal ADR, penilaian keparahan efek samping dan membuat keputusan terapinya, dan pengukuran berat badan rutin dan tes basil tahan asam (BTA) sebagai dasar untuk menilai respon terapi. 13,14 Pada tahap penelitian sebelumnya, juga telah dikembangkan model intervensi berupa model Training-Education-MonitoringAdherence-Networking (TEMAN) Apoteker bagi pasien TB. 15 Model TEMAN Apoteker merupakan model intervensi komprehensif yang terdiri atas lima domain dan dilengkapi dengan enam bentuk tools, antara lain yaitu: modul, booklet, leaflet, poster, lembar dokumentasi pharmaceutical care, dan buku panduan pelaksanaan TEMAN Apoteker.…”
unclassified